Welfare effects of technology-based climate policies in liberalized electricity markets: Seeing beyond total system cost - Sophie Maire; Philippe Thalmann; Frank Vöhringer (Swiss Journal of Economics and Statistics, 2019)
This paper is a contribution to assessing the Swiss energy transition, with an emphasis on the consequences of decommissioning the nuclear power plants for the electricity market and the whole economy. We expect that increased renewable generation and demand-side policies of the type already envisioned will not suffice to close the supply gap, so that Switzerland will have to rely on more imports of electricity, moving away from the export surpluses realized almost every year since 1910. As this reference scenario is contrary to desired energy security, a policy scenario is proposed in which net electricity trade is constrained to balance over the year and the supply gap is closed by relaxing the existing restrictions on gas-fired power plants. One constraint replaces another one, so that the impacts are not obvious. Furthermore, the prices of electricity and natural gas evolve quite differently through time and depend on climate and energy policy. We use a modeling framework coupling a detailed representation of electricity generation and an encompassing representation of the macro-economy to compare these scenarios in terms of both total system cost and welfare. Both indicators favor the reference scenario without gas-fired power plants in spite of its higher marginal costs for electricity. The welfare loss of the policy scenario is small, though, much smaller than the increase in total system cost. This shows that a coupled bottom-up top-down modeling framework assessing the welfare effect of policies can yield very different results from those of an energy system model assessing their impact on total system cost.
Keywords: 330; Climate policy; Energy policy; Electricity markets; Technology restrictions; Soft-link coupling; General equilibrium model; Bottom-up model